2011
DOI: 10.1111/j.1365-2966.2011.19972.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instability in gravitationally stratified plasmas: implications for multiphase structure in clusters and galaxy haloes

Abstract: We study the interplay among cooling, heating, conduction and magnetic fields in gravitationally stratified plasmas using simplified, plane‐parallel numerical simulations. Since the physical heating mechanism remains uncertain in massive haloes such as groups or clusters, we adopt a simple, phenomenological prescription which enforces global thermal equilibrium and prevents a cooling flow. The plasma remains susceptible to local thermal instability, however, and cooling drives an inward flow of material. For p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
457
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(489 citation statements)
references
References 75 publications
(223 reference statements)
28
457
4
Order By: Relevance
“…These earlier analytic models have relied on a simple hypothesis that thermal instabilities would develop if the cooling time (t cool ) is comparable to or smaller than the dynamical time (t ff ) of the gas. However, recent numerical simulations have provided more detailed insights into the process of forming a multi-phase medium (e.g., McCourt et al 2012;Sharma et al 2012). It has been shown that, in fact, a multi-phase medium starts to develop when the cooling time is 3 − 10 times the free-fall time ).…”
Section: Condensing Cool Clouds Due To Thermal Instabilitiesmentioning
confidence: 99%
“…These earlier analytic models have relied on a simple hypothesis that thermal instabilities would develop if the cooling time (t cool ) is comparable to or smaller than the dynamical time (t ff ) of the gas. However, recent numerical simulations have provided more detailed insights into the process of forming a multi-phase medium (e.g., McCourt et al 2012;Sharma et al 2012). It has been shown that, in fact, a multi-phase medium starts to develop when the cooling time is 3 − 10 times the free-fall time ).…”
Section: Condensing Cool Clouds Due To Thermal Instabilitiesmentioning
confidence: 99%
“…Overall, many observational and theoretical studies in the last decade have put the cold feedback mechanism on a very solid ground (e.g., Revaz et al 2008;Pope 2009;Wilman et al 2009;Edge et al 2010;Wilman et al 2011;Nesvadba et al 2011;Cavagnolo et al 2011;Gaspari et al 2012a,b;McCourt et al 2012;Sharma et al 2012a,b;Farage et al 2012;Wagh et al 2013;Li & Bryan 2014a,b;McNamara et al 2014;Voit et al 2015b;Li et al 2015;Prasad et al 2015;Singh & Sharma 2015;Tremblay et al 2015;Valentini & Brighenti 2015;Choudhury & Sharma 2016;Hamer et al 2016;Loubser et al 2016;Meece et al 2016;Russell et al 2016;McNamara et al 2016;Yang & Reynolds 2016b;Barai et al 2016;Tremblay et al 2016). As an example, Gaspari (2015) shows that the AGN-JFM self-regulated by accretion of cold clumps can explain the strong deficit of soft X-ray emission in clusters and groups of galaxies.…”
Section: Closing the Feedback Cyclementioning
confidence: 99%
“…6,7 Theoretical models in which cold clouds precipitate out of the hot gas via thermal instability and accrete onto the black hole exhibit the necessary tuning. [8][9][10] We have recently presented observational evidence showing that the abundance of cold gas in the central galaxy increases rapidly near the predicted threshold for instability. 11 Here we present observations showing that this threshold extends over a large range in cluster radius, cluster mass, and cosmic time, and incorporate the precipitation threshold into a comprehensive framework of theoretical models for the thermodynamic state of hot gas in galaxy clusters.…”
mentioning
confidence: 99%